Hidroquímica e qualidade das águas supeficiais e subterrâneas em áreas sob influência de lavras pegmatíticas nas Bacias dos Córregos Água Santa e Palmeiras, Município de Coronel Murta (MG) - Vanessa Souza Magalhaes (2006)
This work present a physical, chemical and microbiological study of groundwater, spring and stream water of Água Santa and Palmeiras basin from Middle River Jequitinhonha Valley, Coronel Murta (MG). In this place, mineral exploration activitie is developed on pegmatite to extraction of gem, that constitute the main income source of the local population. In contrast with the mineral wealth, the area is placed among the Brazilian regions with the most precarious economic conditions, being extremely important the water scarcity problem with low precipitations and high temperatures averages. Mineral activity and the lack of basic sanitation facility in the village and garimpo constitute potential factors of contamination of the hydric system. In this context, the main goal of this work is to determinate the quality of water in areas of influence of garimpos and parallely, determinate parameters of the potentialities of the hydric system in order to subsidize future action of adjusted handling. The monitoring net implanted for the study is integrated for fifteen sampling points that include springs, surface and groundwaters samples were collected for represent one hydrologic year, with samplings in the dry, rainy and intermediate seasons. The hydrochemical characterization of the springs, surface and groundwaters indicates that the dominant concentration of ions can be related to the alteration of local lithology. The result of electric conductivity and dissolved solids obtained for the water from garimpo of the Palmeiras basin, demonstrate the low salinity of this water. The bicarbonated water is the dominant type. Usually, high value of electric conductivity is associated to the load contaminante in the water, such as high content in nitrate in the garimpo of Água Santa Stream and high content of organic materia in surface water, related to launching of domestic effluent and wastewater. The evaluations of waters quality of both basins disclose physical, chemical and microbiological features in disagreement with the standards for surface waters quality and also with those established for underground waters. Microbiological contaminante is present in all the sampling points. The results gotten in this study demonstrate that the adoption of measures that guarantee the permanent flow and quality of waters of Água Santa e Palmeiras streams are necessary. Examples of these measures are preservation of spring areas; recovery of stream-edge vegetation; implantation of system for collect and treatment of domestic effluents; garbage collection; education related to environmental preservation of water and vegetation, as well as the adequate disposal of mining residues. The points of water occurrence in areas of mineral activities are potential for high quality water captation and, at the same time, they configure a canal of direct contact with thegroundwater system. Of this form, they are necessary hydrodynamic studies and the adoption of measures that guarantee its quality and rational usage.